2014
DOI: 10.1007/s00464-014-3841-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ESD for patients with early gastric cancer and comorbid liver cirrhosis: a propensity score analysis

Abstract: LC patients appear to be good candidates for ESD if they have CP-A liver function and no history of HCC. Although their short-term outcomes were not inferior, the patients with Child-Pugh grades B/C or with histories of HCC benefited less from ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…However, a poorer prognosis is anticipated in patients with severe comorbidities even if successful treatment is achieved. Recently, results similar to ours were reported [8,10,11]. One multicenter retrospective cohort study [8], using propensity score analysis, demonstrated that 5-year overall survival rates of patients with liver cirrhosis was 60.0%, which was significantly lower than that of patients without liver cirrhosis (91.0%).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, a poorer prognosis is anticipated in patients with severe comorbidities even if successful treatment is achieved. Recently, results similar to ours were reported [8,10,11]. One multicenter retrospective cohort study [8], using propensity score analysis, demonstrated that 5-year overall survival rates of patients with liver cirrhosis was 60.0%, which was significantly lower than that of patients without liver cirrhosis (91.0%).…”
Section: Discussionsupporting
confidence: 85%
“…First, this study has sufficient median follow-up duration, 77.3 months in ASA-PS group 1/2 and 67.8 months in ASA-PS group 3, compared with previous studies (33.4-64.0 months) [8,10,11]. Secondly, this study also has a large sample size when Table 2 The cause of death and adverse events before and after propensity score matching Other cancers were detected during the follow-up period after ESD, although patients with history of another malignancy before ESD were excluded ASA-PS American Society of Anesthesiologist Physical Status, pulmonary disease (pneumonia, interstitial pneumonia, respiratory failure), cardiovascular disease (heart failure, ischemic heart disease, aortic dissection), cerebrovascular disease (hemorrhage, infarction), Other types of cancers (after ESD) (colon, lung, liver, bile duct), other diseases (esophageal varix rupture, acute peritonitis, hypoglycemia, senility, accident) a The number of patients who contracted each disease as a comorbidity on treatment and died of the same disease Before matching (n = 488) After matching (n = 178) compared to previous reports [8,10,11]. Thirdly, we demonstrated that the ASA-PS group 3 was an independent risk factor for overall mortality and resulted in shorter patient survival when adjusted for other confounding factors using propensity score matching and IPTW methods.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Endoscopic submucosal dissection (ESD) has become a standard therapy for gastric epithelial neoplasia after the implementation of technical skills and instrumentation [1]. The minimal invasiveness and organ-preserving nature of this technique have allowed for broader applications in higher risk patients such as elderly patients and those with severe comorbidities [2][3][4]. An increase in the ageing population has been associated with a rise in the number of individuals on antithrombotic therapy.…”
Section: Introductionmentioning
confidence: 99%